A 128-Base-Pair Sequence Containing the pac1 and a Presumed Cryptic pac2 Sequence Includes cis Elements Sufficient To Mediate Efficient Genome Maturation of Human Cytomegalovirus - Wang, Jian Ben (American Society for Microbiology, 2011)
Herpesvirus DNA replication proceeds via concatemeric replicative intermediates that are comprised of head-to-tail linked genomes. Genome maturation is carried out by the terminase, an enzyme complex that mediates both the insertion of concatemer DNA into capsids and its subsequent cleavage to release genomes within these capsids. This cleavage is sequence specific, but the governing cis-acting DNA sequences are only partially characterized. Two highly conserved motifs, the pac1 and pac2 motifs, lie near the ends of herpesvirus genomes and are known to be critical for genome maturation. In murine cytomegalovirus, poorly conserved sequences distal to the pac2 motif up to 150 bp from the point of cleavage are also important for cleavage. Here, we sought to identify the cleavage/packaging signals of human cytomegalovirus. Our results show that a previously proposed pac2-like poly(A) tract is dispensable for cleavage/packaging function and suggest that human cytomegalovirus may utilize a cryptic pac2 motif that lacks a poly(A) tract characteristic of pac2 motifs in other herpesviruses. Additional distal sequences 47 to 100 bp from the point of cleavage were found to enhance cleavage efficiency. These results should facilitate the identification of trans-acting factors that bind to these cis elements and elucidation of their functions. Such information will be critical for understanding the molecular basis of this complex process.